(untitled) - Ryan, Thomas P. (Hoboken, N.J., 2007)
Modern Engineering Statistics presents state-of-the-art statistical methodology germane to engineering applications. With a nice blend of methodology and applications, this book provides and carefully explains the concepts necessary for students to fully grasp and appreciate contemporary statistical techniques in the context of engineering.
Keywords: Engineering,Kỹ thuật; Statistical methods,Thống kê các phương pháp